Facial dysostoses: Etiology, pathogenesis and management. Issue 4 (4th October 2013) - Trainor, Paul A.; Andrews, Brian T.; Cox, Timothy C.; Luquetti, Daniela V.; Cunningham, Michael L.
Abstract Approximately 1% of all live births exhibit a minor or major congenital anomaly. Of these approximately one‐third display craniofacial abnormalities which are a significant cause of infant mortality and dramatically affect national health care budgets. To date, more than 700 distinct craniofacial syndromes have been described and in this review, we discuss the etiology, pathogenesis and management of facial dysostoses with a particular emphasis on Treacher Collins, Nager and Miller syndromes. As we continue to develop and improve medical and surgical care for the management of individual conditions, it is essential at the same time to better characterize their etiology and pathogenesis. Here we describe recent advances in our understanding of the development of facial dysostosis with a view towards early in utero identification and intervention which could minimize the manifestation of anomalies prior to birth. The ultimate management for any craniofacial anomaly however, would be prevention and we discuss this possibility in relation to facial dysostosis. © 2013 Wiley Periodicals, Inc.